Chamaejasmin B Decreases Malignant Characteristics of Mouse Melanoma B16F0 and B16F10 Cells - Si, Lingling; Yan, Xinyan; Wang, Yan; Ren, Boxue; Ren, Huanhuan; Ding, Yangfang; Zheng, Qiusheng; Li, Defang; Liu, Ying (Frontiers in Oncology, 2020)
Chamaejasmin B (CHB), a natural biflavone isolated from Stellera chamaejasme L., has been reported to exhibit anti-cancer properties; however, its effect in melanoma cells is not clear. Here, we aimed to investigate the anticancer effect of CHB in mouse melanoma B16F0 and B16F10 cells. We found that CHB significantly suppressed cell proliferation and promoted cell cycle arrest at G0/G1 phase in B16F0 cells; it also induced cell differentiation and increased melanin content by increasing tyrosinase (TYR) activity and mRNA levels of melanogenesis-related genes in B16F0 cells. Meanwhile, wound closure, invasion, and migration of B16F0 and B16F10 cells were dramatically inhibited. Moreover, CHB significantly increased ROS levels and decreased ΔΨm, resulting in B16F0 and B16F10 cell apoptosis. Finally, in vivo studies showed that CHB inhibited tumor growth and induced tumor apoptosis in a mouse xenograft model of murine melanoma B16F0 and B16F10 cells. Overall, CHB decreases malignant characteristics and may be a promising therapeutic agent for malignant melanoma cells via multiple signaling pathways.